Fragilidade financeira das empresas da região noroeste do Rio Grande do Sul: impactos do ciclo de negócios e das suas características individuais - Smolski, Felipe Micail da Silva (2017)
Post-Keynesian literature elaborates a interesting theoretical framework for the understanding of the functioning of the capitalist system, in order to more reliably reflect the interactions of the financial prism with the productive side of economies. This research agenda, prominent in regional development studies, is concerned with understanding how production financing activities, financial contracts between agents, and the business cycle lead to increasing fragilities that flow into recurrent crises and how the uneven creation of currency by the financial system across the territory creates diverse patterns of development. In this sense, the recent Brazilian scenario was surrounded by a major political and economic crisis, which incorporated an unprecedented increase in the default rate of credit operations to legal entities between 2014 and 2015. Therefore, it is of interest for economic development researchers to measure the impacts of crises on regional economy agents. Thus, the purpose of this dissertation is to analyze the associations between the financial fragility of companies in the Northwest region of Rio Grande do Sul with their individual characteristics and the business cycle. As methodology, the statistical technique of logistic regression was applied, with monthly microdata from January 2014 to December 2015, of Banrisul's client firms located in the municipalities of its Northwest Superintendence, with a monthly average revenue higher than R$ 500,000.00. The dependent variable was the occurrence or non-occurrence of delays in the financial system by the companies representing the financial fragility of the agents, using the dichotomy of the Ponzi financial structures and the hedge elaborated by Minsky. As main results, the research hypothesis was confirmed, being that the impacts of the business cycle and the individual characteristic of the firms on the financial fragility of the companies were evidenced. Although the research hypotheses were rejected by the exclusion of variables not important to the models, the main results, using the variables significant to the proposed regression, indicate associations between the financial fragility of local agents, their individual characteristics and economic factors. Above all, during the study period, the chances of being in a Ponzi situation increased for larger companies, as well as those from the transportation, food and education sectors. In addition, there was strong evidence that the Selic interest rate, liquidity preference, and spatial distribution index of bank branches are associated with the probability of defaults.